Cold molecular gas and free–free emission from hot, dust-obscured galaxies at z ∼ 3. Issue 2 (6th June 2020) - Penney, J I; Blain, A W; Assef, R J; Diaz-Santos, T; González-López, J; Tsai, C-W; Aravena, M; Eisenhardt, P R M; Jones, S F; Jun, H D; Kim, M; Stern, D; et al.
ABSTRACT: We report on observations of redshifted CO(1–0) line emission and observed-frame $\rm \sim 30\, $ GHz radio continuum emission from five ultra-luminous, mid-IR selected hot, Dust-Obscured Galaxies (Hot DOGs) at $z\rm \gtrsim 3$ using the Karl G. Jansky Very Large Array. We detect CO(1–0) line emission in all five Hot DOGs, with one of them at high signal-to-noise ratio. We analyse FIR-radio spectral energy distributions, including dust, free–free, and synchrotron emission for the galaxies. We find that most of the $\rm 115\, $  GHz rest-frame continuum is mostly due to synchrotron or free–free emission, with only a potentially small contribution from thermal emission. We see a deficit in the rest-frame $\rm 115\, $  GHz continuum emission compared to dusty star-forming galaxies and sub-millimetre galaxies (SMGs) at high redshift, suggesting that Hot DOGs do not have similar cold gas reserves compared with star-forming galaxies. One target, W2305−0039, is detected in the FIRST $\rm 1.4\, GHz$ survey, and is likely to possess compact radio jets. We compare to the FIR–radio correlation, and find that at least half of the Hot DOGs in our sample are radio-quiet with respect to normal galaxies. These findings suggest that Hot DOGs have comparably less cold molecular gas than star-forming galaxies at lower, $z\rm \sim 2$ redshifts, and are dominated by powerful, yet radio-quiet AGN.